MADRASAH TEACHER PROFESSIONALISM DEVELOPMENT STRATEGY BASED ON SUPHISTIC HUMANISM IN THE AGE OF COMMUNITY 5.0 - Jannah, Raudatul; Sahlan, Moh.; Mukaffan, Mukaffan; Rofi'ah, Siti Hamidahtur (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
The purpose of this study to analyzes strategies for developing the professionalism of madrasa teachers based on Sufistic humanism. This research uses a qualitative approach with data collection techniques using interviews, observation, and documentation. The data analysis used is Miles and Huberman's data analysis. The results show that the teacher professional development strategy has three stages: development planning, implementation, and evaluation. This human research planning model includes, among others, considering HR requirements, comparing demand requirements with HR availability (HR demand, excess HR, and HR shortages), and considering the availability of HR within the organization. The implementation of teacher professionalism development is carried out with several coaching concepts based on sufistic humanism, including pedagogic development, professionalism development, personality development, and social development. While the development evaluation process is carried out with First, evaluation through leadership. Second, evaluation through the teacher by compiling learning tools at the beginning of each new school year. Third, evaluation through the assessment of MTs Al-Qodiri Jember students. This study shows that the policies provided to develop teacher professionalism at MTs Al-Qadiri Jember have an impact on improving teacher quality so that there are more professional teachers in carrying out their duties and responsibilities.